Folic Acid Supplementation in the Gestational Phase of Female Rats Improves Age-Related Memory Impairment and Neuroinflammation in Their Adult and Aged Offspring. (29th November 2020) - Garcez, Michelle Lima; Mina, Francielle; Bellettini-Santos, Tatiani; Ribeiro, Fernanda Melo; Ghisi Frassetto, Alessandra Zanette; Batista-Silva, Hemily; da Luz, Aline Pereira; Schiavo, Gustavo Luiz; Medeiros, Eduarda Behenck; Zabot, Gabriel Casagrande; Canever, Lara; Zugno, Alexandra Ioppi; et al.
Abstract: Folic acid (FA) supplementation is important during pregnancy to avoid malformations in the offspring. However, it is unknown if it can affect the offspring throughout their lives. To evaluate the offspring, female mother rats (dams) were separated into 5 groups: Four groups received the AIN-93 diet, divided into control and FA (5, 10, and 50 mg/kg), and an additional group received a FA-deficient diet, and the diet was performed during pregnancy and lactation. We evaluated the female offspring of these dams (at 2 and 18 months old). The aged offspring fed with FA-deficient diet presented habituation, spatial and aversive memory impairment and the FA maternal supplementation prevented this. The natural aging caused an increase in the TNF-α and IL-1β levels in the hippocampus from 18-month-old offspring. FA maternal supplementation was able to prevent the increase of these cytokines. IL-4 levels decreased in the prefrontal cortex from aged control rats and FA prevented it. FA deficiency decreased the levels of IL-4 in the hippocampus of the young offspring. In addition, natural aging and FA deficiency decreased brain-derived neurotrophic factor levels in the hippocampus and nerve growth factor levels in the prefrontal cortex and FA supplementation prevented it. Thus, the present study shows for the first time the effect of FA maternal supplementation on memory, cytokines, and neurotrophins in the aged offspring.